Acceleration of interstitial lung disease induced by raltitrexed. (July 2020) - Howlett, Sarah; Aul, Raminder; Hill, Mark; Pinato, David J
Introduction: Raltitrexed is a folate analogue, which selectively inhibits thymidylate synthase, used in the treatment of colorectal carcinoma. Common side effects include asthenia and gastrointestinal and haematological toxicities. Case report: We present the case of a 74-year-old gentleman with incidental mild interstitial lung disease on preoperative staging CT Chest who developed acute breathlessness whilst undergoing adjuvant raltitrexed treatment for a completely excised colorectal adenocarcinoma. Management and outcome: Discontinuation of raltitrexed and a course of steroid therapy resulted in resolution of symptoms, mirrored by an improvement in lung function tests. Discussion: The clinical pattern of rapid progression with steroid response highlights the potential for significant acceleration of interstitial lung disease by raltitrexed.